Grammarly and Paraphraser.io in Supporting Rewriting Skills: A Comparative Study - Intan Nia Salsabila; Nabila Shaini Putri; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study compares Grammarly and Paraphraser.io in supporting students’ academic writing and rewriting skills based on Flower and Hayes’s (1981) cognitive process theory, which includes the stages of planning, translating, and reviewing. Using a descriptive qualitative method supported by quantitative data, the research involved 32 English Education students who had used both tools in academic writing. Data were collected through questionnaires and analyzed descriptively to identify students’ perceptions of grammatical accuracy, rewriting ability, feedback quality, and overall writing improvement. The results of this study indicate that 54.4% of students use Grammarly and 45.6% use Paraphraser.io, showing that Grammarly is the slightly more dominant and trusted tool for improving grammatical accuracy and clarity, while Paraphraser.io functions as a complementary platform for paraphrasing and generating new sentence structures; together, both tools contribute effectively though through distinct roles to enhancing students’ academic writing performance. The comparative analysis revealed that Grammarly was most effective in enhancing analytical skills during the planning and reviewing stages, improving grammar, coherence, and clarity. In contrast, Paraphraser.io was most beneficial for generative skills in the translating stage, directly enhancing originality and sentence variation. Most respondents rated their writing improvement highly, confirming the positive impact of both tools on academic performance. In conclusion, the findings confirm that Grammarly and Paraphraser.io serve distinct, yet complementary roles: the former ensures linguistic precision, while the latter supports structural creativity, ultimately helping students produce highly accurate and original academic texts.